GAMBARAN PENGETAHUAN DAN PENGALAMAN MENSTRUASI REMAJA PUTRI DI PROVINSI JAWA TIMUR - Charissa Balqis,; Dwi Handayani,; Yuniar Sulistyo,; Savira Auliya Abdullah, (Jurnal Cakrawala Ilmiah, 2023)
Adolescence is a period of transition from children to adults and adolescents, namely 10-19 years. Adolescence begins with the signs of puberty indicating a maturity of the reproductive organs, female adolescents during puberty are marked by menarche events. In Indonesia in 2012 it showed that the average age of menarche was 13 years, with an earlier occurrence at the age of less than 9 years or later until the age of 17 years, and in East Java Province the average age of menarche was 36.5% at the age of 13-14 years, 2.3% at the age of 9-10 years and 0.1% at the age of 6-8 years. This research is a descriptive quantitative research, namely the description of the results of the research as it is based on the results of observations and also the results of the data obtained. The data collection method in this study is by using a Google form questionnaire. The population in this study were 465 young women in East Java. The sample was taken using cluster random sampling technique. The results and discussion include the characteristics of the respondents, the knowledge of young women on menstruation which obtained the results from 465 East Java respondents who had good knowledge of 165 (35%) respondents and less than 300 (65%) of respondents, including regarding questions regarding menstrual experience. It can be concluded that the knowledge of young women in East Java from 465 respondents as many as 300 respondents have less knowledge about menstruation. Then, from the experience aspect, it was found that young women experienced menstruation the most at the age of 11-14 years (385), and young women were also more dominant in telling and getting information about their menstruation from their parents. Based on the results of the data it was also found that the majority of respondents felt fine (208) during menstruation. With a normal menstrual cycle every month. The majority of respondents stated that the type of pads used was disposable pads (455). Then the majority of respondents said that changing pads was done every 4-5 hours once a day. A total of 297 respondents said that sanitary napkins were not available at their school.